Analgesic effects of maxillary and inferior alveolar nerve blocks in cats undergoing dental extractions. Issue 2 (February 2015) - Aguiar, Joana; Chebroux, Alexandre; Martinez-Taboada, Fernando; Leece, Elizabeth A
The aim of this study was to evaluate the analgesic effects of maxillary and/or inferior alveolar nerve blocks with lidocaine and bupivacaine in cats undergoing dental extractions. Twenty-nine cats were enrolled. Using an adapted composite pain scale, cats were pain scored before the dental procedure and 30 mins, and 1, 2 and 4 h after isoflurane disconnection. Cats were sedated with buprenorphine (20 µg/kg), medetomidine (10 µg/kg) and acepromazine (20 µg/kg) intramuscularly. Anaesthesia was induced using alfaxalone (1–2 mg/kg) intravenously and maintained with isoflurane in oxygen. Each cat was randomly assigned to receive maxillary and/or inferior alveolar nerve blocks or no nerve blocks prior to dental extractions. Each nerve block was performed using lidocaine (0.25 mg/kg) and bupivacaine (0.25 mg/kg). Heart rate, systolic arterial blood pressure, respiratory rate, end tidal carbon dioxide and isoflurane vaporiser settings were recorded 5 mins before and after the dental extractions, and the difference calculated. Group mean differences (mean ± SD) for heart rate (−9.7 ± 10.6 vs 7.6 ± 9.5 beats/min [nerve block vs control group, respectively], P <0.0001), systolic arterial blood pressure (−10.33 ± 18.44 vs 5.21 ± 15.23 mmHg, P = 0.02) and vaporiser settings (−0.2 ± 0.2 vs 0.1 ± 0.4, P = 0.023) were significantly different between groups. The control group had higher postoperative pain scores (median [interquartile range]) at 2 h (3 [1.75–4.00] vs 1 [0–2], P = 0.008) and 4 h (4 [2–6] vs 2 [1–2], P = 0.006) after the dental extractions. Maxillary and inferior alveolar nerve blocks with lidocaine and bupivacaine administered prior to dental extractions resulted in a reduction in heart rate and blood pressure while allowing for a reduction in isoflurane. Cats receiving nerve blocks had lower postoperative pain scores than the group without nerve blocks.